Nitric Oxide Inhibits Al-Induced Programmed Cell Death in Root Tips of Peanut (Arachis hypogaea L.) by Affecting Physiological Properties of Antioxidants Systems and Cell Wall - Pan, Chun-Liu; Yao, Shao-Chang; Xiong, Wei-Jiao; Luo, Shu-Zhen; Wang, Ya-Lun; Wang, Ai-Qin; Xiao, Dong; Zhan, Jie; He, Long-Fei (Frontiers in Physiology, 2017)
It has been reported that nitric oxide (NO) is a negative regulator of aluminum (Al)-induced programmed cell death (PCD) in peanut root tips. However, the inhibiting mechanism of NO on Al-induced PCD is unclear. In order to investigate the mechanism by which NO inhibits Al-induced PCD, the effects of co-treatment Al with the exogenous NO donor or the NO-specific scavenger on peanut root tips, the physiological properties of antioxidants systems and cell wall (CW) in peanut root tip cells of NO inhibiting Al-induced PCD were studied with two peanut cultivars. The results showed that Al exposure induced endogenous NO accumulation, and endogenous NO burst increased antioxidant enzyme activity in response to Al stress. The addition of NO donor sodium nitroprusside (SNP) relieved Al-induced root elongation inhibition, cell death and Al adsorption in CW, as well as oxidative damage and ROS accumulation. Furthermore, co-treatment with the exogenous NO donor decreased MDA content, LOX activity and pectin methylesterase (PME) activity, increased xyloglucan endotransglucosylase (XET) activity and relative expression of the xyloglucan endotransglucosylase/hydrolase (XTH-32) gene. Taken together, it was suggested that endogenous NO triggered by Al might mainly act as a response factor. Exogenous NO alleviated Al-induced PCD by inhibiting Al adsorption in CW, enhancing antioxidant defense and reducing peroxidation of membrane lipids, alleviating the inhibition of Al on root elongation by maintaining the extensibility of CW, decreasing PME activity, and increasing XET activity and relative XTH-32 expression of CW.